ENTREATY OF FUZZY INTERVAL-VALUED EDAS METHOD IN ORDER PREFERENCE OF CUSTOMERS FOR RANKING OPTIMIZATION. - Jaleesha, B K; Ezhil, S Shenbaga (Malaysian Journal of Computer Science, 2023)
The growing need of a research lab in automotive confirmatory tests is increasing day by day in the competitive market. Testing plays an important part in time and cost to meet the durability and quality requirements of the customers. Decision Making Models [DMM] with order preference supports well in optimizing the process scheduling time and utilization of machines. The analyzed data is of with multi-criterion constraints and unreliable parameters. As the constraints in analyzed data belongs to [-R, R], the problem is modelled with generalized Fuzzy Interval Valued set. The defined FIVs are justified using Novel Accuracy of Membership and Non-Membership values. The unconventionality of the work discussed in this paper is applying FIVs in the existing Evaluation by Distance Average Sum [EDAS] method. The weight values of the criterion are calculated using the Average Distance [AD] formula. In general, Fuzzy VIKOR and Fuzzy TOPOSIS helps in identifying the closeness co-efficient of the parameters. Particularly, VIKOR plays a vital role on group utility and TOPOSIS on Max/Min of negative and positive ideal solutions respectively. Here, the proposed FIVEDAS method is framed with the Relative Distance Values [RDA] and so it provides us an ideal ranking in order preference. The results are compared with the existing lab process utility time in First-Come-First Serve method.